ON METHODS AND RESULTS OF THE EXPERIMENTS CONDUCTED IN CHILDREN’S SHOPPING MALLS GAME ROOMS - G. I. Rudchenko; D. V. Tekushin; A. G. Nikitin (Современная наука и инновации)
The article presents the results of research, how do the parameters of the children’s evacuation from children’s playrooms influence on the overall process of evacuation from shopping malls.